2016
DOI: 10.1097/qai.0000000000000965
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: HIV Infection Is Associated With Worse Bone Material Properties, Independently of Bone Mineral Density

Abstract: Low bone mineral density (BMD) in HIV-infected individuals has been documented in an increasing number of studies. However, it is not clear whether it is the infection itself or the treatment that causes bone impairment. Microindentation measures bone material strength (Bone Material Strength index) directly. We recruited 85 patients, 50 infected with HIV and 35 controls. Median Bone Material Strength index was 84.5 (interquartile range 83-87) in HIV-infected patients and 90 (88.5-93) in controls (P < 0.001). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 28 publications
3
22
1
Order By: Relevance
“…There was no difference in BMSi values between men and women in the group of acromegaly patients and in the control group. Although skeletal health has been shown to differ between the sexes, this observation is in keeping with other data on BMSi previously reported by our group (16) and another group (30), and partly in keeping with a study that investigated male and female HIV patients and controls and observed lower BMSi values in female HIV patients compared to male patients but comparable BMSi values between male and female controls (31).…”
Section: Discussionsupporting
confidence: 92%
“…There was no difference in BMSi values between men and women in the group of acromegaly patients and in the control group. Although skeletal health has been shown to differ between the sexes, this observation is in keeping with other data on BMSi previously reported by our group (16) and another group (30), and partly in keeping with a study that investigated male and female HIV patients and controls and observed lower BMSi values in female HIV patients compared to male patients but comparable BMSi values between male and female controls (31).…”
Section: Discussionsupporting
confidence: 92%
“…The recent development of bone microindentation has opened the possibility of testing the ability of bone to resist the impact of a tiny probe in creating microscopic cracks in the surface of cortical bone. Several clinical experiments have shown worse microindentation properties in groups of patients as type 2 diabetes mellitus (Farr et al, 2014), fracture in patients with osteopenia (Malgo et al, 2015), HIV-infected individuals (Guerri-Fernandez et al, 2016), or glucocorticoid-treated patients (Mellibovsky et al, 2015) in spite of a relatively preserved or normal BMD. Therefore the technique captures some of the non-density components of bone strength with the advantage of potentially being applicable in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The number of patients in whom BMSi was measured varied greatly between studies, with the smallest study including only seven subjects (68) and the largest 489 subjects (41). All studies were performed in adults with ages ranging from a median of 33.9 years (27.6-53.8 years) (46) to a mean of 78.3 ± 1.1 years (51). Fourteen studies included only women (35, 37-43, 48-51, 55, 68), and four studies included only men (54,63,64,69).…”
Section: Characteristics Of Studies Generated By the Searchmentioning
confidence: 99%